2002
DOI: 10.2214/ajr.178.4.1780915
|View full text |Cite
|
Sign up to set email alerts
|

Directed Biopsy During Contrast-Enhanced Sonography of the Prostate

Abstract: Contrast-enhanced transrectal sonography improves the sonographic detection of malignant foci in the prostate. The performance of multiple biopsies of suspicious enhancing foci significantly improves the detection of cancer. There is no advantage to additional examination of the gland after bolus administration of contrast material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 16 publications
1
31
0
2
Order By: Relevance
“…The cancer detection rate with transrectal US-guided biopsies was described to be from 10 to 50% in different studies [18,48]. Although our sample size is small, it seems that the obtained results of MRI-guided biopsies are comparable or superior to US-guided biopsies in patients with previously negative US-guided biopsies.…”
Section: Discussionmentioning
confidence: 71%
“…The cancer detection rate with transrectal US-guided biopsies was described to be from 10 to 50% in different studies [18,48]. Although our sample size is small, it seems that the obtained results of MRI-guided biopsies are comparable or superior to US-guided biopsies in patients with previously negative US-guided biopsies.…”
Section: Discussionmentioning
confidence: 71%
“…These reports demonstrate not only a high diagnostic potential and reliability of CE-US, but also a high safety profile of US-CAs; in adults, anaphylactoid reactions have been reported at a low rate of less than 0.002% [53,54]. The established indications are oncological, traumatic or inflammatory lesions, assessment of vascular patency or pathology, tissue perfusion, echocardiography, intraoperative guidance and transplant queries [32,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Although CE sonography does not seem to affect the performance of sonography for cancer detection in this study, we suggest that improved sensitivity for cancer detection according to biopsy site may be helpful in guiding sonographically guided biopsy. Previous studies have shown that CE sonographically guided targeted biopsy detects as many cancers as systemic biopsy with fewer than half the number of biopsy cores and that a combination of CE sonographytargeted biopsy and systemic biopsy could increase the cancer detection rate [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual merit of sonographic contrast material may be in question because the performance of CE sonography varied in those studies. The variable degree of cancer risk in the study populations of previous studies may be largely responsible for the variable results of those studies; patients with a high PSA level and positive digital rectal examination may have a greater chance of having positive sonographic findings than those with an indeterminate risk of prostate cancer [9][10][11][12][13][14]. Therefore, if CE sonography were shown to have improved performance over gray-scale or color Doppler sonography for the detection of cancer in a strictly designed patient population with indeterminate risk, the impact of CE sonography would become much stronger.…”
Section: Contrast-enhancedmentioning
confidence: 99%